African livestock genetic resources and sustainable breeding strategies: Unlocking a treasure trove and guide for improved productivity - Ibeagha-Awemu, E.M.; Peters, S.O.; Djikeng, Appolinaire; Rege, J.E.O. (Springer, 2025)
This open access book is a rich resource that chronicles the abundant livestock genetic resources in Africa. Organized in five sections, the chapters trace special productive and adaptive attributes of African livestock breeds, past breed improvement efforts, capacity building and strategies to effective utilization of available genetic resources in the era of modern technologies. The authors cover major farm animal groups as well as dromedaries, rabbits and grasscutters.